O olhar político-pedagógico do professor de escola pública com relação às condições da produção do conhecimento do aluno - Santos, Adenilton Lima dos (2018)
The idea of analyzing some variables of teachers' political-pedagogical gaze in the face of social relations involving learning becomes necessary in the face of a political and social conjuncture that will prove unfavorable to the education and the purposes of the public school in particular. The learning relationships that are established in the school go through different and subtle values variables about what the teacher thinks of their students and all interfere in the learning of the student. Some of these variables about what teachers think about their students are conceived as the most striking ones about improving the learning climate. The curriculum and influences suffered or caused by such visions will be present and will be analyzed in this dissertation, in order to clarify how the teacher's actions are impacting even if unconscious through them. The teacher training filled with historical and ideological aspects collaborate to a better understanding of the teaching performance and how it is shaped within the space and its curricular practices. Knowing the teacher's commitment and his / her attitudes to recognize fundamental behaviors for the teaching / learning process, will collaborate to clarify the complexity of its practice. This research, presented here, starts from the hypothesis that social, economic and political variables are the most striking in the teacher's view as determinants of the quality of learning and its effectiveness. But it was also part of the hypothesis that the interferences of affection within the class, family as value-giver and individual commitment also make up the determinants of school performance and personal interest in learning and how the teacher guides his pedagogical decisions. Research instruments were assembled through a questionnaire that allowed the answers of teachers from three public networks in the metropolitan region of São Paulo to map some values that may interfere with their practices and students' learning. It was sought here to obtain from the teachers a position on the social impacts on the learning climate and on its relations with the sense of school. From the analysis of the data it was found that in the view of teachers it is not the social causes that appear as major determinants of the success or failure of student learning, but it is their internal dispositions, their commitment and discipline that, in fact, matter in their yield for good learning